379 Human Endogenous Retrovirus-K (HML-2) Contributes to a Unique Stem-Cell Niche in Glioblastoma. (April 2023) - Shah, Ashish Harish; Rivas, Sarah; Doucet-Ohare, Tara; Govindarajan, Vaidya; DeMarino, Catherine; Ampie, Leonel; Banasavadi-Siddegowda, Yeshavanath; Maric, Dragan; Suter, Rob; Lee, Myoung-hwa; Zaghloul, Kareem A.; Walbridge, Stuart; et al.
Abstract : INTRODUCTION: Human Endogenous Retrovirus (HERV) are ancestral viral relics that comprise nearly 8% of the human genome. Although silenced in normal tissues, the most recently integrated provirus HERV-K (HML-2) can be pathologically reactivated in certain cancers. METHODS: We utilized a combination approach using scRNA-seq, multiplex immunofluorescence, and TEM to characterize HERV-K expression in malignant gliomas. Using CRISPR engineering and CHIP-qPCR, we downregulated HML-2 in both patient-derived glioma neurospheres and intracranial orthotopic models and identified interactions between HERV-K and pluirpotency transcription factors. RESULTS: We identified pathological expression of HML-2 in human malignant gliomas in CSF (HERV-K DNA/RPP30 = 35.2 ± 8.8 vs 23.1 ± 6.7, n = 18, p = 0.02) and tumors (HERV-K RNA/HPRT mean = 1.15 ± 0.2 vs. 0.5 ± 0.2, p = 0.01, n = 20) compared to epilepsy controls. Aberrant HML-2 expression corresponded to a unique stem-cell niche using multivoxel automated segmentation. Using a tailored scRNA-seq sequencing pipeline, we identified glioblastoma cellular populations with elevated HML-2 transcripts in neural progenitor-like cells that can drive cellular plasticity (ANOVA, p < 0.001). Using CRISPR technology, we demonstrate that HML-2 is critical to maintenance of glioblastoma stemness and tumorigenesis in both glioblastoma neurospheres and intracranial orthotopic murine models (OS: 26 days vs. 18.6, p=0.0008, n=20). Downregulation of HERV-K using CRISPRi reduces the glioblastoma neurosphere formation (2-way ANOVA, p < 0.0001) and HERV-K env, Polymerase, OCT4 and Nestin transcripts (2-way ANOVA p < 0.001). Moreover, using Transmission Electron Microscopy, we discovered that some glioma stem-cells form immature retroviral virions in glioblastoma. Inhibiting HML-2 expression with nucleoside reverse transcriptase inhibitors reduces extracellular reverse transcriptase (One-way ANOVA, p < 0.05), tumor viability (IC50 = 75.8-123.1 uM), and pluripotency (1-way ANOVA, p < 0.01). CONCLUSIONS: Our results suggest that HML-2 is overexpressed in the glioblastoma stem-cell niche. Since persistence of glioblastoma stem-cells is considered responsible for treatment resistance/recurrence, HML-2 may serve as a unique therapeutic target in glioblastoma.